Enhancing Motivation and Achievement through Gamified Learning in Vocational Electropneumatic Education - Elvina; Fadhilah; Fahmi Rizal; Asrul Huda (Jurnal Penelitian Pendidikan IPA, 2025)
This study investigates the influence of gamified learning using Quizizz on students’ motivation and academic achievement in Electropneumatic Control Systems at a vocational high school. The research was conducted in response to low student motivation and academic performance in complex technical subjects. A quasi-experimental design with a non-equivalent pretest-posttest control group was employed. The experimental group (n = 25) received gamified instruction via Quizizz, while the control group (n = 24) was taught using conventional methods. Data were collected using a validated motivation questionnaire (34 items) and a learning outcome test (38 items). Gain scores (posttest minus pretest) were analyzed using Independent Samples t-Test. Results revealed that the experimental group had significantly higher motivation scores (t = 4.396, p < 0.05) and better academic achievement (t = 3.275, p < 0.05) compared to the control group. These findings suggest that incorporating gamification strategies into technical instruction can effectively enhance both student motivation and academic outcomes.